Standardized reporting and quantification of whole-body MRI findings in children with chronic non-bacterial osteomyelitis treated with pamidronate - C. M. Andreasen; R. F. Klicman; T. Herlin; E. M. Hauge; A. G. Jurik (BMC, 2022)
Abstract Objectives The objectives were to assess changes in radiological disease activity in children with chronic non-bacterial osteomyelitis (CNO) receiving pamidronate therapy and to test a modified radiological index for non-bacterial osteitis (mRINBO) in CNO. mRINBO was used for standardized reporting and quantification of whole-body MRI (WBMRI) findings resulting in an individual summary patient score. Methods WBMRI was retrospectively assessed in 18 children with CNO at baseline and after receiving pamidronate therapy for one year. Parameters of interest were: number and anatomic site of radiologically active bone lesions (RAL), size of RAL, extramedullary affection, spinal involvement and changes in mRINBO, which includes both the number and maximal size of RAL (RALmax) in addition to extramedullary and chronic changes. Results At the time of diagnosis, the mean age of the children was 9.8 (sd, 8.7-10.9) years and 11/18 were females. The number of RALs per patient decreased from median [interquartile range] 4.5 [3-8] to 3 [2-5] RALs per patient (p = 0.02) and extramedullary inflammatory changes regressed. Sixty-one percent of all RALs occurring at baseline resolved and three children became without active inflammatory lesions by WBMRI. The median size of RALs did not change when taking new lesions occurring in 7/18 children into account, but RALmax decreased significantly from 39 [29-45] mm at baseline to 28 [20-40] mm (p < 0.01) at year-one with a concomitant decrease of mRINBO from a median of 5 [4-7] to 4 [3-5] (p = 0.05). Conclusions Pamidronate therapy resulted in a decrease of mRINBO from baseline to year one. mRINBO may be a potential scoring method to quantify changes in radiological disease activity in children with CNO. However, further studies are needed to test feasibility and validity of mRINBO.